Milk Phospholipid Profiling Among Japanese Women with Differing Docosahexaenoic Acid Levels. Issue 2 (30th May 2021) - Ueno, Hiroshi M.; MacKenzie, Andrew; Scott, Dawn; Higurashi, Satoshi; Toba, Yasuhiro; Kobayashi, Toshiya
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: To characterize the milk phospholipids (PLs) profile using phosphorus-31 nuclear magnetic resonance ( 31 P-NMR) and to investigate the effect of elevated milk docosahexaenoic acid (DHA) levels on PLs profiles in Japanese mothers. Methods: Milk samples from eligible patients with high and low DHA from a former cross-sectional study (n = 20; n = 10 for each group) were included. Fifteen milk PLs were analyzed using 31 P-NMR, and the profiles were compared group-wise using Mann–Whitney U -test. The P value of <0.05 was considered statistically significant. Results: The median DHA content in milk was 1.13% and 0.29% for the high and low milk DHA groups, respectively. Twelve PLs, excluding lysophosphatidylserine, cardiolipin, and phosphatidylglycerol, were detected in all participants with 100% positive results. The median concentrations and proportions of total PLs, sphingophospholipids, and glycerophospholipids were comparable between groups. The proportions of choline-containing glycerophospholipid were significantly higher in the high milk DHA group than that in the low milk DHA group (24.09% [median, interquartile range: 23.08%–26.38%] and 21.41% [20.74%–22.84%], P = 0.019). Although the proportions of phosphatidylinositol were significantly lower in the high milk DHA group than that in the low milk DHA group (6.62% [5.75%–6.72%] versus 7.63% [7.11%–8.16%], P = 0.002), while that of phosphatidylcholine (21.90% [18.51%–23.22%] versus 19.78% [18.17%–20.26%], P = 0.059) and alkyl-acyl phosphatidylcholine (0.60% [0.40%–0.74%] versus 0.33% [0.14%–0.51%], P = 0.059) were higher in the former than that in the latter. Conclusions: Our results were comparable to that of the previous literature. Large variations in the milk DHA might affect the composition of choline-containing glycerophospholipids in Japanese mothers. However, possible confounders were not excluded in the study populations.